Pre-lacteal feeding practice and its associated factors among less than twenty-four months old children in Degahbour town, Somali region, Ethiopia - Berhanu, Beruk; Ismaile, Ahmed Mahamed (Journal of Science and Development, 2024)
Prelacteal foods might not be safe due to high risk of contaminating them with biological entities, which can cause infection in the newborn and might affect the colostrum intake. However, in a nation like Ethiopia where diverse cultural practices are prevalent, this might vary depending on the context. Therefore, the aim of this study was to assess prelacteal feeding practice and its associated factors among children under 24 months old in Degahbour town, Somali region, Ethiopia. Methods: A community-based cross-sectional study was conducted from June 5 to July 30, 2021. Data were collected from 300 mothers with children under 24 months of age in Degahbour town by following systematic random sampling method. Bivariable and multivariable logistic regression analyses were performed in order to determine the factors associated with prelacteal feeding practices. Result: 47.3%, 95% CI (42.0%, 53.3%) of the mothers had given prelacteal foods to their newborn baby in the first three days of their life. Being a mother living in semi-urban area [AOR: 4.49 (95% CI 2.39,8.42)], delivered at home [AOR=2.15, 95% CI: (1.21,3.82)], lately initiated breastfeeding for indexed child after the first hour of delivery [AOR=2.34, 95% CI: (1.28,4.28)], not receiving counseling about breastfeeding [AOR = 2.23, 95% CI: (1.28,3.88)], not received ANC follow-up [AOR:2.11; 95%CI (1.19,3.74)], had poor maternal knowledge about breastfeeding [AOR:5.51; 95%CI (3.16,9.62)] were identified as factors associated with practicing prelacteal feeding. Conclusion: In comparison to the regional level figure of 38.8 % and nationally (7.9%) reported in the 2016 EDHS, the prevalence of prelacteal feeding practice is high in Degahbour town. Therefore, to reduce prelacteal feeding practice focus should be placed on initiatives that can enhance institutional delivery, ANC follow-up, and improve mothers' understanding of nutrition throughout their pregnancies, particularly the significance of colostrum feeding right away after delivery.